Association study of NAT2 rs1799931 polymorphism with male infertility - Thanh Thuy, Nguyen; Tien Duc, Pham; Huu Dinh, Tran; Thuy Duong, Nguyen (Vietnam Journal of Biotechnology, 2023)
Infertility is a complex disease that is characterized by the failure to achieve pregnancy after 24 months of regular, unprotected sexual intercourse. Various factors result in male sterility, including genetic and non-genetic factors. Recently, scientists have drawn attention to the role of metabolic genes in contributing to the risk of male infertility by inducing reactive oxygen species (ROS). However, such studies about N-acetyltransferase 2 (NAT2), an enzyme that participates in phase II metabolism, remain limited. Thus, this study investigated whether the NAT2 rs1799931 variant was associated with idiopathic male sterility in Vietnam. A total of 306 DNA samples (148 cases and 158 controls) were genotyped using the polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) methods. About 20% of randomly selected samples were confirmed using an allele-specific polymerase chain reaction (AS-PCR). The results showed that genotype frequencies were consistent with Hardy-Weinberg Equilibrium. Notably, there was an association between NAT2 rs1799931 and male infertility in two genetic models: the additive model (GA genotype, OR = 0.606, 95% CI: 0.369–0.989, p-value = 0.044) and the dominant model (GA+AA genotypes, OR = 0.614, 95% CI: 0.382–0.981, p-value = 0.040). This study has enriched our knowledge about the roles of genetic factors in contributing to male infertility in the Vietnamese population.